EFFORTS TO IMPROVE LEARNING ON LONG JUMP THROUGH MODIFICATION OF THE GAME IN CLASS V STUDENTS OF MI AL-AKBAR SAWAHAN NGEMPLAK BOYOLALI - Nuruddin Priya Budi Santoso; Teguh Santosa; Joko Sulistyono, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2024)
This research aims to determine the increase in squatting long jump ability in class V students at MI Al-Akbar Sawahan Boyolali. This research uses the Classroom Action Research (PTK) method which consists of four stages, namely planning, implementation, observation and reflection in each cycle. This research was completed in two cycles. The research subjects were 21 class V MI Al-Akbar Sawahan Boyolali students. The students consisted of 14 male students and 7 female students. This research data was obtained through a squat long jump skill test through observation. The overall value of the squat long jump material, both practical and theoretical tests, namely cognitive, affective and psychomotor, increased. From the cognitive score, the average pre-cycle class score was 59.52 to 69.94 in cycle I and increased to 80.35 in cycle II. The psychomotor score from the average pre-cycle class score was 64.58 to 71.72 in cycle I and increased to 80.05 in cycle II. The affective value of the average pre-cycle class value was 57.6 to 74.28 in cycle I and increased to 84.28 in cycle II. Student learning outcomes in psychomotor in the complete category were 100% or 21 students, and affective scores in the complete category were 95% or 20 students, and for cognitive scores in the complete category they were 100% or 21 students.